The Process Church of the Final Judgment: The Demise by Transmutation and Replacement of a Controversial New Religion - Cusack, Carole M. (International Journal for the Study of New Religions, 2020)
This article examines a new religious movement (NRM) founded by charismatic leaders in the mid-1960s from the viewpoint of its demise. The Process Church of the Final Judgment was founded in 1966 in London by Mary Ann MacLean and Robert de Grimston. The Process developed a theology melding esoteric Biblical motifs with psychoanalysis. The Process ceased to exist two decades later due to changes in belief and affiliation; members adopted other, mainstream, identities. De Grimston was expelled from The Process in 1974, after which it transformed into The Foundation Faith of God under MacLean’s leadership. The Foundation Faith of God later morphed into the Best Friends Animal Society in Kanab, Utah, abandoning a religious identity in favour of an animal rights-based identity. Until recently little attention was paid to how NRMs ended; the academic focus was overwhelmingly on the origins of such groups. This study builds on new research to argue that The Process ended via activities of transmutation and replacement. In 2020 The Process is a defunct religion with extensive online archives, curated by exmembers and enthusiasts. Processean ideas are kept “alive” and potentially able to be revived; the status of virtual communities and attempted revivals is also discussed with regard to identifying the precise date of the demise of NRMs.